1997
DOI: 10.1080/01411599708220062
|View full text |Cite
|
Sign up to set email alerts
|

Electrical effects accompanying the phase transitions in ethanol cryocondensed thin layers

Abstract: The behaviour of the surface potential of ethanol layers deposited on a cooled substrate was studied. A spontaneous surface potential increase was detected for samples deposited at temperatures close to the well known phase transition (crystallization to crystal I phase) temperature. The activation energy for crystallization was estimated to be 20.7 f 0.4 kl/mol. In addition, thermally stimulated current (TSC) spectra were measured. It was suggested that the amorphous ethanol condensed below 125 K might exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Molecules from the gas phase condense into a solid when they come in contact with a sufficiently cold substrate. If the molecules are polar, i.e., they have a dipole moment, and the substrate temperature is below a certain threshold, the condensate exhibits an electric potential difference between the side in contact with the substrate and that on the outside. This phenomenon was first reported 40 years ago , but has not been studied extensively. Alcohols, in particular, have been examined on a few occasions. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules from the gas phase condense into a solid when they come in contact with a sufficiently cold substrate. If the molecules are polar, i.e., they have a dipole moment, and the substrate temperature is below a certain threshold, the condensate exhibits an electric potential difference between the side in contact with the substrate and that on the outside. This phenomenon was first reported 40 years ago , but has not been studied extensively. Alcohols, in particular, have been examined on a few occasions. , …”
Section: Introductionmentioning
confidence: 99%
“…Alcohols, in particular, have been examined on a few occasions. [3][4][5][6]13 The primary motivation for studying spontaneous polarization is a scientific curiosity, i.e., the desire to answer the question what makes neutral molecules pile up on a cold substrate in such a way that they exhibit a net voltage across the thickness of the layer. Which molecules will generate large voltages and which ones small?…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the decades, few studies [2][3][4][5][6][7][8] had tried to quantify and explain the phenomenon. In recent years, interest has grown and several publications [9][10][11][12][13][14][15][16][17][18][19] have attempted to provide a mechanism for the generation of this astonishing result. The phenomenon has been studied more extensively for water.…”
Section: Introductionmentioning
confidence: 99%
“…Vapor deposition is used to prepare thin films of metals, semiconductors, and dielectrics in a vacuum, and it has wide-ranging applications across many fields for the development of functional materials. Thin-film growth of molecules (e.g., H 2 O, CO, CO 2 , NH 3 , CH 4 , and CH 3 OH) at low temperatures is also key to understanding the formation in cold interstellar regions at around 10 K of icy dust grains, which are the starting material for the evolution of planetary systems. In 1969, Elliott et al reported the buildup of surface potential during the condensation of water vapor on the surface of a liquid-nitrogen trap . The electrical properties of molecular-solid thin films at low temperatures have been widely investigated for decades, and many polar molecules develop a surface potential during vapor deposition on a cold substrate: for example, H 2 O, CO, , NO, N 2 O, ,, SO 2 , NH 3 , halocarbons (CHCl 3 , CF 3 Cl, , CF 2 Cl 2 , CFCl 3 , CHCl=CCl 2 , and o -C 6 H 4 Cl 2 ( ortho -dichlorobenzene)), and organic compounds (acetone, , toluene, , propane, isopentane, isoprene, methyl formate, , ethyl formate, 2,5-dihydrofuran, and alcohols (C n H 2 n +1 OH, n = 1–5) including isobutanol , ); see also review articles. , N 2 O has been extensively studied by Field and co-workers ,,, because it exhibits a clear change in its surface potential. A positive surface potential of about +11 V was reported for 355 monolayers (MLs) of polycrystalline N 2 O at 40 K (+32 mV per ML), which corresponds to an electric field of about 10 8 V m –1 . ,, The authors also reported that the substrate temperature strongly affected the development of the surface potential, with a potential of only about +1 V developing for 355 MLs of polycrystalline N 2 O at 65 K.…”
mentioning
confidence: 99%
“…IR-MAIRS allows this approach to be extended to combination studies that include surface potential measurements, and the approach is applicable to all polar molecules studied previously, as well as nonpolar molecules, including those with anisotropic molecular shapes (e.g., linear alkanes). ,,, Further combination studies using these molecules will provide insights into the origins of the anisotropic molecular orientation and partial dipole alignment during vapor deposition of molecules on cold substrates. IR-MAIRS measurements should also help to reveal the fine structures of solid molecules (e.g., H 2 O) that are important to astrophysics at low temperatures because many of these molecules form amorphous solids in cold interstellar regions.…”
mentioning
confidence: 99%